Comparison of Inhibitory Effect of Curcumin Nanoparticles and Free Curcumin in Human Telomerase Reverse Transcriptase Gene Expression in Breast Cancer - Nosratollah Zarghami; Abbas Rami; Fatemeh Kazemi-Lomedasht (Tabriz University of Medical Sciences, 2013)
Purpose: Telomerase is expressed in most cancers, including breast cancer. Curcumin, a polyphenolic compound that obtained from the herb of Curcuma longa, has many anticancer effects. But, its effect is low due to poor water solubility. In order to improve its solubility and drug delivery, we have utilized a β-cyclodextrin-curcumin inclusion complex. Methods: To evaluate cytotoxic effects of cyclodextrin-curcumin and free curcumin, MTT assay was done. Cells were treated with equal concentration of cyclodextrin-curcumin and free curcumin. Telomerase gene expression level in two groups was compared by Real-time PCR. Results: MTT assay demonstrated that β-cyclodextrin-curcumin enhanced curcumin delivery in T47D breast cancer cells. The level of telomerase gene expression in cells treated with cyclodextrin-curcumin was lower than that of cells treated with free curcumin (P=0.001). Conclusion: Results are suggesting that cyclodextrin-curcumin complex can be more effective than free curcumin in inhibition of telomerase expression.